Special endurance of highly qualified judoists and the method of its quantitative assessment in preparation for responsible competitions - Shiyan, V. V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to substantiate methods for assessing the level of development of special endurance of wrestlers on the basis of a comprehensive definition of pedagogical and biochemical indicators characterizing the effectiveness of performing a standard specific task with throws of a wrestling dummy.